Clarifying the Contours of the Police Legitimacy Measurement Debate: a Response to Cao and Graham - Trinkner, Rick (Asian journal of criminology, 2019)
With the emergence of police legitimacy as a major indicator of good policing, scholars have continued to push our conceptual understanding of this construct. In recent years, a debate has emerged about whether four factors—lawfulness, procedural justice, distributive justice, and effectiveness—are possible sources of legitimacy judgments (Tyler in Annual Review of Psychology 57, 375-400, 2006) or actual components of legitimacy (Tankebe in Criminology 51, 103-135, 2013). My goal in the present paper is review the contours of this debate.